Reliability assessment of thick high strength pipelines with corrosion defects - U. Bhardwaj (2019)
This paper assesses the reliability of thick, high strength corroded pipelines subjected to internal pressure by firstorder reliability algorithms and Monte Carlo simulation methods. First, the predictions of different burst strengthmodels, including a new prediction model for thick high strength pipelines are compared with experimentalresults. Model uncertainty factors are derived for intact and corroded pipelines to calibrate and introduce theuncertainties on the models used in the prediction of structural reliability. The uncertainty associated withmodel uncertainty factors is addressed and the best fitting distribution is identified. Extensive reliability andsensitivity analyses are carried out on intact and corroded pipes with calibrated burst strength models. Throughsensitivity analyses performed for increasing levels of corrosion defects, the influence of basic parameters on theburst strength of corroded pipelines is characterized. The results demonstrate that the model uncertainty factorsand the depth of corrosion are relatively important variables for corroded pipelines. The results obtainedthrough reliability assessment are compared with that obtained by the strength model proposed in the RAMPIPEguidelines